Effects of Housing Environmental Characteristics on Pneumonia Occurrence in Under-Five-Year-Old Children in South Tangerang City - Thresya Febrianti; Ayunda Larasati; Munaya Fauziah (Universitas Airlangga, 2021)
Background: Pneumonia is an ongoing public health problem in Indonesia, ranking as the second most prevalent disease in South Tangerang. Purpose: This study aimed to examine the physical housing environment characteristics in relation to pneumonia occurrence rates among children under-five years of age in South Tangerang City. Method: This research was carried out as a quantitative study with a case-control study design. The population consisted of children under five who were diagnosed with pneumonia at Public Health Center (PHC) of Pamulang and PHC of Ciputat Timur between January 2017 and March 2018. The data were analyzed using the chi-square statistical test. Results: The following characteristics of the housing environment were shown to be associated with pneumonia are bad routines of opening windows (p = 0.00; OR = 11; 95% CI = 2.59–46.78), location of the kitchen is in similar area with other rooms (p = 0.04; OR = 4.03; 95% CI = 1.20–13.53), unqualified humidity in the house (p = 0.05; OR = 3.86; 95% CI = 1.18–12.60), unqualified light intensity in the house (p = 0.01; OR = 9.04; 95% CI = 1.74–46.89), unqualified ventilation area (p = 0.02; OR = 4.50; 95% CI = 1.38–14.82), and unqualified occupancy (p = 0.03; OR = 4.84; 95% CI = 1.29–18.26). Conclusion: The community needs to maintain the physical environment in their houses, such as by opening the windows in the morning so that light comes in and the house does not get damp.